Online Title Management System / Wong Sze Khai - Wong, Sze Khai (2002)
All undergraduates of the Faculty of Computer Science and Information Technology, University of Malaya are required to carry out a final year project in computer or information technology related topic. The project is a compulsory subject for undergraduates in order to complete their degree studies during their three years in the university. This final year project attaches two semesters and brings out nine credit hours out of the total hundred and twenty credit hours. My thesis was named Online Title Management System (OTMS). I was doing the project under the supervision of Puan Miss Laiha Mat Kiah and moderated by Encik Rosli Sall eh. The main objective of the project is to implement a computerize system for managing the thesis titles for WXES!f 3181: Projek Ilmiah I. The main target users for the system are lecturers and undergraduates. This system will be keep track by the administrators assigned by FSKTM. Online Title Management System is divided into three different modules, which are the Administrator module, Lecturer module and Student/visitor module. Generally, the Administrator module will be responsible for security control, which is keeping track of the user accounts and performing thesis title management. In the meantime, the Lecturer module allows users to access the database and performing thesis title management (compare, add, delete, update and search). Last but not least, the Student/visitor module lets the users to search and browse for related information. This project is very important to all the undergraduates because it gives us the opportunity to apply whatever knowledge we have learnt during the pass two years. Beside that, we can also gain knowledge from the literature review done and produce a complete and formal report.